2017
DOI: 10.1242/jeb.153056
|View full text |Cite|
|
Sign up to set email alerts
|

Flight control of fruit flies: dynamic response to optic-flow and headwind

Abstract: Insects are magnificent fliers that are capable of performing many complex tasks such as speed regulation, smooth landings and collision avoidance, even though their computational abilities are limited by their small brain. To investigate how flying insects respond to changes in wind speed and surrounding optic flow, the open-loop sensorimotor response of female Queensland fruit flies (Bactrocera tryoni) was examined. A total of 136 flies were exposed to stimuli comprising sinusoidally varying optic flow and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The time constant of this decay was similar to the value we obtained by fitting our model. Summation of cues from different modalities has been proposed previously to explain stabilization reflexes [34,35] and forward velocity control [26,36,37] in flies and fish. Summation of visual and odor information has been observed in turning behavior of tethered flies [38], and in the turn probability of freely moving larvae [7].…”
Section: Discussionmentioning
confidence: 99%
“…The time constant of this decay was similar to the value we obtained by fitting our model. Summation of cues from different modalities has been proposed previously to explain stabilization reflexes [34,35] and forward velocity control [26,36,37] in flies and fish. Summation of visual and odor information has been observed in turning behavior of tethered flies [38], and in the turn probability of freely moving larvae [7].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Engels placed bumblebees in heavy turbulence to observe the changes in their aerodynamic forces, moments, and flight power [23]. In addition, Lawson investigated the thrust and abdomen pitch of Queensland fruit flies in headwind [24]. In a different study, Ortega-Jimenez [25] even studied how turbulent convective flows impair the flight performance of Drosophila.…”
Section: Introductionmentioning
confidence: 99%
“…Visual control of forward flight in insects is commonly studied using flight tunnels in free-flight (David, 1982;Fuller et al, 2014;Serres et al, 2008;Srinivasan et al, 1996) or tethered-flight settings (David, 1978;Lawson and Srinivasan, 2017). Recent efforts by the authors also demonstrated the potential of using flight mills to study forward flight in semi-free settings with controlled flight conditions (Hsu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%